Assessing service quality : satisfying the expectations of library customers - Hernon, Peter (American Library Association, 2010)
If libraries are to succeed, they must see themselves in competition with other institutions and sources of information--especially the Web--and make customers feel welcome and valued. This classic book is brought fully up to date as Peter Hernon and Ellen Altman integrate the use of technology into the customer experience. They offer solid, practical ideas for developing a customer service plan that meets the library's customer-focused mission, vision, and goals, and challenge librarians to think about customer service in new ways. --from publisher description